Pengaruh Harga Bahan Baku, Harga Jual dan Produksi Terhadap Hasil Penjualan Nasi Bakar Sultan (Studi Kasus UMKM Sambel K'Diyah): (Studi Kasus UMKM Sambel K’Diyah) - Dian Nur Millah; Hendri Sucipto; Slamet Bambang Riono (Al-Buhuts, 2024)
This research aims to analyze the influence of raw material prices, selling prices and production on the sales results of Sultan's roasted rice at Sambel K'Diyah MSMSe. This research was carried out by conducting field observations using a questionnaire as a research instrument with the aim of finding out sales results in the related focus, namely Sambel K'Diyah MSMSe. Sampling in the research used a probability sampling method with a sample size of 93 people. The primary data obtained is a nominal data scale which is then converted into an interval data scale using the method of successive intervals. The data results obtained with the questionnaire instrument were tested using SPSS (Statistical Product and Service Solutions) 25.0. Several tests carried out to analyze the data that have been obtained are correlation tests, reliability tests, multiple linear regression tests, t tests and f tests. The results of the research show that the price of raw materials has an influence on sales results, the selling price has an influence on sales results and production has an influence on sales results, and in this research there is a significant value between the three independent variables and the dependent variable, which can be interpreted as the price of raw materials , selling price and production have a simultaneous effect on the sales results of sultan’s roasted rice in Sambel K'Diyah MSMSe.